Opowieść ciała — ciało opowieści. Jak dojrzewała słowiańska epopeja Juliusza Słowackiego? - Ciechańska, Magdalena (Starość i młodość w literaturze i kulturze, 2016)
The aim of the article is to present an evolution unrealized of Juliusz Słowacki’s creation the “dramaticchronicles”. The variations about Polish nation’s fairy-tale and Slavic World’s past matured in the Słowacki’smind from ‘Ariosto style’ of Balladyna, through a drama Lilla Weneda, to the story of the King-Ghostwho wanders through successive incarnations. The Słowacki’s idea has evolved since the theatrical story,in which the poet leads a sophisticated game with the reader, to the mistical poem with desire to writeabout the universe and the laws running it. One of the main points of the analysis will be an aspect ofphysicality and suffering in the above mentioned works and their relation with deteriorating Juliusz Słowacki’sphysical condition.